Effects of epiphytic and exogenous lactic acid bacteria on fermentation quality and microbial community compositions of paper mulberry silage - Cheng, Qiming; Li, Maoya; Fan, Xueying; Chen, Yulian; Sun, Hong; Xie, Yixiao; Zheng, Yulong; Chen, Chao; Li, Ping (Frontiers in Microbiology, 2022)
This study aimed to isolate, characterize, and identify lactic acid bacteria (LAB) strains from various sources and evaluate their effects on the nutritional quality, fermentation characteristics, and microbial compositions of paper mulberry (PM) after 60 days of ensiling. Forty-nine LAB strains were isolated from Phalaris arundinacea silage, pickle, and fresh PM leaves; three of these strains (Lactiplantibacillus plantarum, YC1; Levilactobacillus brevis, PC3; and Lactiplantibacillus plantarum, BP17) and one commercial inoculant Gaofuji (GFJ) were subsequently used. Compared with other treatments, PC3 and BP17 increased (P < 0.05) the LAB count and crude protein content and decreased (P < 0.05) the molds and coliform bacteria counts, pH, and ammonia-N content of PM silages. BP17 and PC3 increased the relative Lactiplantibacillus abundance and decreased that of Lelliottia and Cladosporium, improving PM silage quality. Therefore, PC3 and BP17 can improve the fermentation quality of PM silage and could be used as silage starter cultures.